Decoding your dog : the ultimate experts explain common dog behaviors and reveal how to prevent or change unwanted ones - Horwitz, Debra; Ciribassi, John; Dale, Steve, 1957-; Neilson, Jacqueline C.; Herron, Meghan Elaine; Melese, Patrick Yves; Houpt, Katherine A.; Cooper, Leslie Larson; Gaskins, Lori; Flannigan, Gerrad; Lindell, Ellen M.; Berger, Jeannine; et al. (Boston : Houghton Mifflin Harcourt, 2014)
The top dog behaviorists in the country - the top researchers, scientists, and veterinarians - have teamed up with a renowned media personality to create the most cutting-edge, scientifically accurate, definitive book on the most popular behavioral issues that dogs face.--
Can't we just talk? -- Choosing your new best friend -- Creating a Mensa dog -- Housetraining 101 -- Tools of the trade -- School days -- I know they're normal behaviors, but how do I fix them? -- Lassie and Timmy: kids and dogs -- All dogs need a job -- Aggression unleashed: do dogs mean to be mean? -- Loyalty gone overboard: separation anxiety -- I know it's going to rain, and I hate the Fourth of July -- Tail chasing, leg licking -- can't you stop? -- Dogs with an AARF card: growing old with grace.
Includes index.
Keywords: Dogs -- Behavior; Dogs -- Training; Human-animal communication; Dogs; Behavior, Animal; Dogs -- Behavior; Dogs -- Training; Human-animal communication